Examining the Effect of AFAD Training on Science Teacher Candidates' Perceptions towards Natural Disasters - Zihni, Zeynep Alemdar; Yüzüak, Ahmet Volkan; Öcal, Merve; Yüzüak, Ahmet Volkan (My University, 2025)
The primary aim of this research is to determine the awareness of science teacher candidates regarding natural disasters. This research aims to reveal the level of awareness towards natural disasters before and after the education received by science teacher candidates. The participant group of the study consists of 19 science teacher candidates studying at the faculty of education of a public university. Based on the findings, it can be concluded that science teacher candidates have a high perception and awareness of natural disasters. Despite being final-year students, the participants have not attended additional training on this subject, even though natural disasters are quite frequent in our country, indicating a lack of sufficient studies in this area. In this context, it is believed that organizing preparatory and awareness-raising trainings related to natural disasters in faculties of education could provide significant contributions in terms of emotional control and disaster prevention, and that the knowledge and skills of science teacher candidates could be utilized in potential natural disasters.
Keywords: Education.; Natural disasters; Science teacher candidates; AFAD training program